PENGEMBANGAN LKS BERBASIS PERMAINAN KARTU DOMINO UNTUK PENINGKATAN HASIL BELAJAR KOGNITIF SISWA - Widiarto, Mahendra; Hajiriah, Titi Laily; Armiani, Sucika (Bioscientist : Jurnal Ilmiah Biologi, 2019)
Based on the results of preliminary observations at SMP Negeri 10 Mataram shows that students are less involved in the learning process, students tend to be passive and their interest in learning is not optimal due to the lack of variation in the use of instructional media by teachers and have never used the media of domino cards. Therefore, through the development of a domino card based worksheet it is hoped that it can improve student cognitive learning outcomes. This research is a research development with the aim to determine the shape and feasibility of student worksheets (LKS) based on domino cards. Student worksheets (LKS) based on domino cards are student worksheets with the substance of natural science material that are more interesting and enjoyable to learn than other media because this domino card game fosters excessive curiosity and is challenged to seek statements with right answers. The development model in this study is the 4-D model of Thiagarajan, Semmel and Semmel (1974) which consists of 4 stages, namely: 1) Define; 2) Design; 3) Develop; and 4) Disseminate. In this study only three stages were carried out, namely the define, design and develop stages. The role of the validator will be requested after the develop stage is completed. The results of this study obtained an average score of expert validation results of 78.33%. The results of the analysis of the implementation of this device obtained a presentation by students at 94% with a very practical category and from the analysis of the teacher in terms of practicality of the device by 70% with a practical category while the cognitive learning outcomes of students with classical completeness were 80%. Based on the results of the study it can be concluded that the development of a domino card-based worksheet can improve student cognitive learning outcomes.